Transformasi Kearsipan Dinamis Terintegrasi melalui Teknologi di Sekretariat Daerah Kabupaten Sekadau - Petrus Atong; Emiliani Nindy Diana Rusega Sim; Mita Elisabet (Universitas Kapuas Sintang, 2026)
This research examines how the implementation of technology in the Integrated Dynamic Archiving Information System (SRIKANDI) at the Regional Secretariat of Sekadau Regency has changed the way archives are managed. The purpose of this study is to evaluate how well SRIKANDI functions in improving transparency and efficiency in archive management, speeding up document searches, and digitizing archives to support more efficient government administration. This research was conducted thru a descriptive qualitative field study with interviews with relevant sources, such as the Regional Secretary, Head of the General Affairs Section, and the SRIKANDI Administrator. Research shows that SRIKANDI successfully reduced the time spent manually searching for documents. Documents and archives can be stored digitally with this system, improving security, ease of access, and data transparency. Additionally, SRIKANDI accelerates decision-making and optimizes administrative processes. However, there are issues such as employes not yet understanding digital technology and disruptions due to unstable internet connections. These obstacles add to the time required to complete administrative tasks and disrupt the smooth operation of the system in some areas. This study found that SRIKANDI helps modernize archive management in the Regional Secretariat of Sekadau Regency, although there are some issues that need to be addressed. Therefore, continuous training and improvement of technological infrastructure are needed for this application to work better in the future to support effective and transparent government administration.